Integrating Technology in the Fight Against Human Trafficking: Challenges, Opportunities, and Social Implications - Moses Adeolu AGOI; Sain, Zohaib Hassan; Oluwanifemi Opeyemi AGOI (Journal of Social Studies and Education, 2024)
This research focuses on the role of technology in detecting and supporting the recovery of victims of human trafficking. In a global context, human trafficking is a complex and hidden crime, which is often difficult for authorities to tackle. Technology, such as artificial intelligence (AI) and facial recognition, is increasingly relied upon to identify victims and improve response speed in the recovery process. This study uses a qualitative research design with a case study approach to explore how technology is applied by law enforcement agencies and non-governmental organizations (NGOs). The main data sources were obtained through in-depth interviews, observations, and documentation from various sources who were directly involved in efforts to utilize technology in combating human trafficking. The results show that technology, despite its challenges in terms of implementation and sustainability, has proven to be effective in raising public awareness, speeding up the detection process, and supporting victim recovery through the provision of safe and accessible services. The implications of this study show that the integration of technology can strengthen prevention and rehabilitation efforts in dealing with human trafficking, while empowering the community to play a more active role in reporting such incidents. With ever-evolving technological advancements, opportunities to eradicate human trafficking are increasingly open, providing hope for previously neglected victims.